Complete plastome sequence of Eustoma grandiflorum (Gentianaceae), a popular cut flower. Issue 2 (3rd July 2019) - Yan, Jingyan; Cao, Qian; Wu, Zesi; Chen, Shaofeng; Wang, Jiuli; Zhou, Dangwei; Xie, Jiuxiang
Abstract: Eustoma grandiflorum (Raf.) Shinners is a popular cut flower due to its beautiful morphological characteristics and extended vase life. Here, the complete plastome sequence of E. grandiflorum was reported based on the Illumina HiSeq Platform. The plastome sequence is 154, 230 bp in length with a typical quadripartite structure, containing a pair of inverted repeated (IR) regions (25, 755 bp) that are separated by a large single copy (LSC) region of 84, 297 bp, and a small single copy (SSC) region of 18, 423 bp. A total of 130 functional genes were annotated, including 84 protein-coding genes, 38 tRNA genes, and 8 rRNA genes. The complete plastome sequence of E. grandiflorum will provide a valuable resource for its garden utilization and the phylogenetic studies of Gentianaceae.